International Migration 2019 Wall Chart - Nations Unies (United Nations, 2019)
International Migration 2019 wall chart provides up-to-date information on global estimates of the number of international migrants for all countries and areas of the world, disaggregated by age, sex, country of origin and country of destination. This wall chart is based on the latest data on international migration for 232 countries and areas of the world from the 2019 revision of the International Migrant Stock dataset, covering the period from 1990 to 2019.